2023
DOI: 10.21037/jgo-22-599
|View full text |Cite
|
Sign up to set email alerts
|

Tailored chemotherapy for colorectal cancer peritoneal metastases based on a drug-screening platform in patient-derived organoids: a case report

Abstract: Background: Peritoneal metastasis from colorectal cancer (CRC) has limited therapeutic options and poor prognosis. Systemic chemotherapy combined with cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) or pressurized intraperitoneal aerosol chemotherapy (PIPAC) have yielded initial promising results. However, standard local therapies with oxaliplatin and mitomycin are not optimal and a better individualized management of these patients remains as an unmet clinical need. Patientd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Combination therapies take this personalization to the next level. In colorectal cancer, a combination of targeted therapies may be used to simultaneously block multiple signaling pathways that drive the disease . For instance, dual inhibition of the EGFR and HER2 pathways has shown promise in preclinical studies.…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapies take this personalization to the next level. In colorectal cancer, a combination of targeted therapies may be used to simultaneously block multiple signaling pathways that drive the disease . For instance, dual inhibition of the EGFR and HER2 pathways has shown promise in preclinical studies.…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%
“…In colorectal cancer, a combination of targeted therapies may be used to simultaneously block multiple signaling pathways that drive the disease. 222 For instance, dual inhibition of the EGFR and HER2 pathways has shown promise in preclinical studies. Additionally, combining targeted therapies with immunotherapy can enhance the body's immune response against the tumor, improving treatment outcomes.…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%
“…In a recent case report, Prieto et al reported that they performed a low-throughput drug screen (treatment of organs with 5-FU, SN-38 (7-ethyl-10-hydroxycamptothecin, the active metabolite of the DNA topoisomerase I inhibitor irinotecan), or oxaliplatin), using patient-derived organoids prior to the patient undergoing a second, personalized, intraperitoneal chemotherapy session, and found that 5-FU and SN-38 showed strong cytotoxicity, while oxaliplatin was less cytotoxic. They also found that 5-FU and SN-38 showed strong cytotoxicity, whereas oxaliplatin had much lower cytotoxicity, suggesting that the best therapeutic results could be achieved by using these two drugs in this intraperitoneal chemotherapy . In addition, they showed that the chances of obtaining a beneficial outcome for the patient are significantly greater if the organoid is modeled at an early stage of carcinogenesis.…”
Section: Clinical Treatment Options For Peritoneal Metastatic Cancermentioning
confidence: 99%
“…They also found that 5-FU and SN-38 showed strong cytotoxicity, whereas oxaliplatin had much lower cytotoxicity, suggesting that the best therapeutic results could be achieved by using these two drugs in this intraperitoneal chemotherapy. 81 In addition, they showed that the chances of obtaining a beneficial outcome for the patient are significantly greater if the organoid is modeled at an early stage of carcinogenesis.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%